Laporan Kasus Pansitopenia Pada Infeksi Malaria Falsiparum - Luh Dina Yulita; Yusuf Aulia Rahman (CV. Jasa Sukses Abadi, 2020)
Malaria is a life-threatening infectious disease caused by parasites that are transmitted to people through the bites of infected female Anopheles mosquitoes or through blood transfusion. Malaria is an endemic disease that still remains a major health problem in the world. The authors report a case of 21-years old man who presented with intermittent fever and pancytopenia without any signs of spontaneous bleeding that had a history of travel to a malaria endemic area. The diagnosis of malaria is made through examination of peripheral blood morphology. These findings highlights the importance for clinicians to consider tropical malaria diagnosis in patients with acute infection and presented with pancytopenia. Management of this patient included administration of anti-malaria drugs, transfusion of PRC, enteral nutrition, adequate fluids administration, antibiotics in the condition of leukopenia, and administration of other symptomatic therapies. The clinical condition and laboratory findings gradually improved after six days of hospitality.